Sanitation facilities, hygienic conditions, and prevalence of acute diarrhea among under-five children in slums of Addis Ababa, Ethiopia: Baseline survey of a longitudinal study. - Metadel Adane; Bezatu Mengistie; Helmut Kloos; Girmay Medhin; Worku Mulat (PLoS ONE, 2017)
Background In developing countries, children under the age of five years who live in slums are highly vulnerable to diarrhea. However, there is a paucity of information on the relationship between sanitation facilities and hygienic conditions to acute diarrhea among under-five children in slum areas of Addis Ababa, Ethiopia. Therefore, this study examines the sanitation facilities and hygienic conditions in the slums of Addis Ababa and identifies the main factors significantly associated with acute diarrhea among children aged 0-50 months in those slums. Methods A community-based cross-sectional household survey was carried out between September and November 2014, that then served as the baseline survey of a longitudinal study. For this survey, 697 children aged 0-50 months were recruited from two slum districts in Addis Ababa. A pre-tested structured questionnaire and an observational checklist were used for data collection. Multivariable logistic regression analysis was used to identify sanitation facilities and hygiene-related factors that were significantly associated with acute diarrhea by controlling potential confounding effects of selected socio-demographic factors. Adjusted odds ratio (AOR) with corresponding 95% confidence interval (CI) was used to quantify the strength of association. Main findings The prevalence of acute diarrhea among children aged 0-50 months in the study area was 11.9% and 94.6% of the sanitation facilities were unimproved. Sharing of a sanitation facility by six or more households (AOR = 4.7; 95% CI: 2.4-9.4), proximity of sanitation facilities within 15 meters of homes (AOR = 6.6; 95% CI: 2.5-17.0), presence of feces (AOR = 3.9; 95% CI: 1.5-10.3) and flies (AOR = 2.5; 95% CI: 1.3-5.0) on the floor of and/or around sanitation facilities, and presence of uncollected garbage inside house compounds (AOR = 3.2; 95% CI: 1.2-8.4) were significantly associated with acute diarrhea. Conclusion This study reveals the slum environment to be high risk for diarrhea due to close proximity of sanitation facilities to homes, sharing of sanitation facilities, and poor hygiene of the sanitation facilities and housing compounds. We recommend the development of a comprehensive diarrheal disease prevention program that focuses on improving the cleanliness of the sanitation facilities and housing compounds. Increasing the number of improved sanitation facilities at an appropriate distance from houses is also essential in order to reduce the number of households that share one latrine.